Recent Advances & Applications of Nanotechnology in Diabetes - Harsoliya, M.S. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Nanotechnology is an advanced scientific technique that provides more accurate and timely medical information for diagnosing disease. Diabetes mellitus (DM) is a commonly seen chronic disease, which seriously threatens the health of human beings. Nanotechnology is a focal point in diabetes research, where nanoparticles in particular are showing great promise in improving the treatment and management of the disease. Due to their ability to potentially enhance drug delivery to areas where there are barriers or unfavorable environments for macromolecules, nanoparticles are being explored as vehicles for improved oral insulin formulations. The use of nanotechnology in the development of glucose sensors is also a prominent focus in non-invasive glucose monitoring systems. Nanotechnology can now offers new implantable or wearable sensing technologies that provide continuous and extremely accurate medical information. The purpose of this is to throw more light on the recent advances and impact of nanotechnology on biomedical sciences to cure diabetes. Nanomedicine, the application of nanotechnology to medicine, has already offered some new solutions, and many pharmaceutical companies are trying to develop targeted drug delivery using nanotechnology and already existing drugs. Nanotechnology offers some new solutions in treating diabetes mellitus. Boxes with nonporous that protect transplanted beta cells from the immune system attack, artificial pancreas and artificial beta cell instead of pancreas transplantation, nanospheres as biodegradable polymeric carriers for oral delivery of insulin are just some of them. Use of nanotechnology in diabetes is development of oral insulin, microsphere for oral insulin production. This review concluded that nanotechnology will be effective therapy in diabetes.